Minimizing Production Costs Through Aggregate Production Planning with Compromise Strategy in the Food Industry - Saputra, Dafid Mega; Hernadewita, Hernadewita; Hendra, Hendra (Jurnal Teknologi, 2024)
The food industry is required to carry out production efficiency by minimizing production costs and maintaining competitiveness in the market. One approach that has proven effective in optimizing the production process is through the application of aggregate production planning. This research aims to design a compromise production planning strategy by considering various factors that influence production costs in the food industry, achieve efficiency, and reduce production costs significantly. This research uses an aggregate production method through a compromise strategy model approach to order data for a year. The research results showed that there were two production planning alternatives, namely the first alternative is variable constant labour with overtime, required additional production costs of IDR 338,080,241, while the second alternative is workforce variations, required additional production costs of IDR 301,229,167. The second production alternative can be chosen to be implemented in production planning due to it requires lower costs. Through this study, it is expected that it can provide a valuable contribution to practitioners and academics in understanding the important role of aggregate production planning in achieving production cost efficiency goals in the food industry